Single-Case Experimental Design for Evaluating Basic Reading Interventions for Students With Learning Disabilities: An Illustrative Case. (February 2023) - Berkeley, Sheri; Hock, Michael; Washburn, Jocelyn
Many students with learning disabilities (LD) do not master basic reading skills, which affects later reading fluency and reading comprehension development. Single-case experimental design (SCED) research yields unique opportunities to better understand which aspects of a basic reading intervention are effective with a particular student, including the individual's rate of growth, stability, or maintenance of acquired skills, and whether or not modifications need to be made to the intervention under study. In this article, we use a case study illustration to highlight unique considerations for using SCED research to investigate basic reading interventions for students with LD. Finally, we provide a discussion of future directions and a potential shift in SCED methodology that is responsive to the comprehensive and multiple skill nature of reading instruction.